Standard specification for electric-resistance-welded carbon steel heat-exchanger and condenser tubes. (American Society for Testing and Materials, 2005)
This specification2 covers minimum-wall-thickness, electric-resistance-welded, carbon steel tubes to be used for heat exchangers, condensers, and similar heat-transfer apparatus.